A utilização do triângulo retângulo na astronomia - NOGUEIRA, Alex Brendo Ferreira (2023)
This article aims to show that the shape of the rectangular triangle and its properties were used to measure distances, such as the earth-sun and earth-moon distances. The text is divided into four sections: the first contains an introduction; the second section is intended to present a brief background on solar system models; in the third is the object of mathematical trigonometry in the right triangle; and the last section is responsible for demonstrating how the calculations of the distances of certain points were made using the right triangle.